Characterization and Genome Analysis of a Nicotine and Nicotinic Acid-Degrading Strain Pseudomonas putida JQ581 Isolated from Marine - Li, Aiwen (Mar Drugs, 2017)
The presence of nicotine and nicotinic acid (NA) in the marine environment has caused great harm to human health and the natural environment. Therefore, there is an urgent need to use efficient and economical methods to remove such pollutants from the environment. In this study, a nicotine and NA-degrading bacterium—strain JQ581—was isolated from sediment from the East China Sea and identified as a member of Pseudomonas putida based on morphology, physio-biochemical characteristics, and 16S rDNA gene analysis. The relationship between growth and nicotine/NA degradation suggested that strain JQ581 was a good candidate for applications in the bioaugmentation treatment of nicotine/NA contamination. The degradation intermediates of nicotine are pseudooxynicotine (PN) and 3-succinoyl-pyridine (SP) based on UV, high performance liquid chromatography, and liquid chromatography-mass spectrometry analyses. However, 6-hydroxy-3-succinoyl-pyridine (HSP) was not detected. NA degradation intermediates were identified as 6-hydroxynicotinic acid (6HNA). The whole genome of strain JQ581 was sequenced and analyzed. Genome sequence analysis revealed that strain JQ581 contained the gene clusters for nicotine and NA degradation. This is the first report where a marine-derived Pseudomonas strain had the ability to degrade nicotine and NA simultaneously.